Increased intrahepatic quasispecies heterogeneity correlates with off-treatment sustained response to nucleos(t)ide analogues in e antigen-positive chronic hepatitis B patients. (February 2016) - Chen, L.; Gan, Q.R.; Zhang, D.Q.; Yao, L.F.; Lin, R.S.; Li, Q.; Lin, M.H.; Yu, D.M.; Zhang, X.X.; Pan, C.
Abstract: Finite treatment with nucleos(t)ide analogues (NAs) remains a great challenge for chronic hepatitis B in the clinic. This study aimed to investigate the relationship between intrahepatic quasispecies heterogeneity and the NAs off-treatment outcomes in a prospective cohort. Eighteen HBeAg-positive patients with chronic hepatitis B who achieved the cessation criteria underwent liver biopsy, and stopped treatment thereafter. Patients were followed up prospectively for 1 year. The reverse transcriptase (RT) gene of intrahepatic hepatitis B virus (HBV) was cloned and sequenced. Intrahepatic quasispecies heterogeneity and specific gene mutations were analysed using bioinformatic methods. Ten patients achieved sustained response, and eight patients developed viral relapse. The intrahepatic quasispecies Shannon entropy and nucleotide diversity within either RT or the surface (S) region of patients with sustained response were significantly higher (p < 0.05) than those of patients who had a viral relapse. Intrahepatic quasispecies Shannon entropy at the nucleotide level predicted the sustained off-treatment response (area under receiver operating characteristics curve 0.925; 95% CI 0.807–1.000; p 0.003). More positive selection sites and N -glycosylation mutations within the S region were found in patients with sustained response than in the patients with viral relapse (p < 0.01). Most of the positive selection sites in patients with sustained response were located in reported HLA-I-restricted or HLA-II-restricted epitopes. Intrahepatic quasispecies heterogeneity at the end of treatment was correlated with off-treatment outcomes in HBeAg-positive patients with chronic hepatitis B. More immune escape mutations were found within the S region in patients with sustained response. The higher intrahepatic quasispecies heterogeneity indicated a more robust immune control over HBV, which in turn maintained a sustained response after withdrawal of NAs.